Lessons from Chinese History: Translation as a Collaborative and Multi-Stage Process - St. André, James (TTR, 2010)
This paper examines how the development of translation practice under the influence of Buddhism, and also in the late Qing (1890-1911), serve to highlight two neglected areas of research in Translation Studies. First, there is the issue of the extent to which translation is a collaborative process. In both time periods, collaboration among 2 to 1000 people was the norm. Yet the models proposed in “classic” Translation Studies in the twentieth century theorized the translation process as being accomplished by a lone individual. The recent growth of translation companies has shown that collaboration is still common today, yet this remains a “black hole” in terms of research. Second, in both periods in China, relay translation through “pivot” languages played a vital role in the translation process. Again, this is a phenomenon that has been downplayed in Translation Studies; relay has been seen as a necessary evil, in a sense replicating the stigma attached to translation itself. These two phenomena thus deserve further study and have implications for translation pedagogy.